Experience of the Early Penile Fracture Repair: A Cross-Sectional Study in A Tertiary Care Center (Journal of Dhaka Medical College, 2024)
Background: Penile fracture is a surgical emergency and most often it can be diagnosed clinically. But delayed presentation due to the embarrassing nature of the injury makes surgical outcome worse. Objectives: This study was conducted to compare results of early and delayed surgical interventions of patients presenting with penile fracture. Methodology: A cross-sectional study was conducted at the department of Urology, in Dhaka Medical College of hospital, Bangladesh from 30th July 2018 to 30th January 2020. Twenty- Seven (27) patients with penile fracture were enrolled in this study. They were diagnosed on the basis of history and clinical findings. They were divided into two groups; early presenter (15 patients) who came within 24 hours and delayed presenter (12 patients) who came after 24 hours. Among the early presenters, 13 patients had unilateral corporeal injury and 2 patients had bilateral corporeal injury. On the other hand, in delayed presenters, 11 patients had unilateral corporeal injury and 1 patient had bilateral corporeal injury. Surgical repair was done in all patients. Results: Patient age range was between 15 to 60 years. The commonest presenting complaints were cracking sound 26 out of 27 (96.30%), penile swelling 24 out of 27 (88.88%), pain 22 out of 27(81.48%) and detumusence during sexual intercourse or an erection 17 out of 27(62.96%), urethra bleeding 3 out 27(11.1%). Among different causes, vigorous intercourse where female on top (62.9%) was the commonest followed by bending during erection (18.5%), masturbation (11.1%) And rolling over bed (7.4%). Out of 15 patients in early group, patients presented with urethral injury. The complications in delayed repair group were, plaque formation 3 out of 15 (20%); penile shaft deformity 2(13.3%); erectile dysfunction 1(6.6%) and skin necrosis 2 (13.3%). But in early repair group only one patient developed skin necrosis which was managed conservatively. Conclusion: Fracture of the penis is a surgical emergency. Immediate surgical repair gives excellent results even in the presence of urethral injury. Early diagnosis by history and clinical examination and timely surgical intervention is essential for better outcome with minimal longterm complications.J Dhaka Med Coll. 2022; 31(2) : 210-214